(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The article discusses the breeding biology of Cyprinus carpio communis.The fish is a late spring spawner and has only one spawning period during the year.Gonad growth coincides with gradual increase in water temperature and day length.30 specimens were collected from Dal(Srinagar) and Wular(Sopore)lakes from March 2021 to July 2022 with the help of local fisherman.The specimens ranged from 26.560 to 180.14 gm in weight,11.8cm to 28.1 cm in total length.The fecundity varied from from 7710 in a fish measuring 11.8cm(TL) to 110,585 in a fish measuring 28.1cm(TL).The results indicates that the fish is a high fecund one and is thus well establish fish in lakes of Kashmir.